Manipulating Weyl quasiparticles by orbital-selective photoexcitation in WTe2 - Meng-Xue Guan (Nature Portfolio, 2021)
Photoexcitation in Weyl semimetals is recently reported to induce topological phase transitions useful for ultrafast switching devices. Here, the authors predict that the symmetry of the atomic orbitals comprising the Weyl bands in response to linear light polarization allows for not only annihilation but also separation of Weyl quasiparticles.